A novel digital fuzzy system for image edge detection based on wrap-gate carbon nanotube transistors. (October 2020) - Bozorgmehr, Ali; Khaleqi Qaleh Jooq, Mohammad; Moaiyeri, Mohammad Hossein; Navi, Keivan; Bagherzadeh, Nader
Highlights: A digital fuzzy approach for image edge detection is proposed. This method employs simple fuzzy rules for digital image edge detection. Simple logic gates based on carbon nanotube transistor are used for implementation. Delay and power are significantly reduced while a reasonable accuracy is provided. Graphical abstract: Abstract: This study presents a novel digital fuzzy approach for image edge detection based on carbon nanotube field effect transistor (CNTFET). The proposed design employs a simple fuzzy rule for digital image edge detection. To investigate the functionality and performance of the proposed fuzzy approach, our results are compared with the MATLAB edge detection operators such as Sobel, Canny, and Prewitt. Based on the simulation results, we demonstrate that the proposed fuzzy approach can be implemented through nanoscale logic gates and provide a reasonable accuracy. The core element of the proposed fuzzy system, implemented with CNTFETs, occupies 0.22 µm 2 layout area and consumes 535 nW power consumption. Our results also emphasize the benefits of the Gate-All-Around (GAA) CNTFETs as a potential candidate for nanoscale digital fuzzy image processing applications.